1026. MECONOPSIS WANBAENSIS SUBSP. UNDULATISSIMA: Papaveraceae. (15th March 2022) - Rankin, David W. H.; Chambers, Anne
Summary: Meconopsis wanbaensis subsp. undulatissima D. W. H. Rankin, a new subspecies from the south‐west part of Sichuan Province of China, is described and illustrated. The description of M. wanbaensis T. Yoshida is revised and its relationships with other members of Meconopsis Vig. section Grandes Fedde series Integrifoliae Grey‐Wilson are discussed.